Effect of Dietary Supplementation with Spirulina platensis and Moringa oleifera as Alternatives to Antibiotics on Growth Performance, Carcass Traits and Cost-Effectiveness in Broiler Chickens - Hossain, Md Mufazzal; Hossain, Md Imran; Naser, Abu; Beg, Md Anwarul Haque; Rahman, Md Abdur (Research in Agriculture Livestock and Fisheries, 2025)
A study was conducted to determine the comparative and combined efficacy of Moringa oleifera dry leaf powder and Spirulina platensis powder as natural feed additives on productive performance and cost-effectiveness in broilers, in comparison to an antibiotic-based diet. Accordingly, a total of 120-day-old Lohmann Meat broiler chicks were randomly assigned to four treatment groups using a completely randomized design, with three replicates, each containing 10 chicks. Among the four treatment groups, one group was fed a basal diet supplemented with antibiotics and served as the control, while the other groups were fed the same diet supplemented with 2% Moringa leaf powder, 1% Spirulina powder, and 1% Moringa leaf powder with 0.5% Spirulina powder. The results of the experiment indicated that the combined addition of Moringa and Spirulina powder improved the growth performance of broilers. However, no significant differences (P > 0.05) were found in final live weight, feed intake, body weight gain, and feed conversion ratio among the treatment groups. The synergistic effect of these natural feed additives significantly (P < 0.05) increased the weights of breasts, drumsticks, wings, livers, intestines, hearts, and dressing percentage compared to other treatments. However, no significant differences (P > 0.05) were observed in breast, back, neck, gizzard, or spleen weight among any of the groups. Overall, the present study suggests that the combined effect of Moringa and Spirulina positively influenced broiler performance and cost-effectiveness. Therefore, it can be concluded that these two natural feed supplements can be utilized as alternatives to antibiotics. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 219-230